SIMULATION MODELS FOR USE IN THE LEARNING PROCESS - Jo'rakulov Jasur Javhar og’li (Bright Mind Publishing, 2025)
This article highlights the importance and effectiveness of using simulation models in the educational process. Simulation models allow students to consolidate theoretical knowledge with practical experience, make decisions in real conditions, and model various situations. In fields such as engineering, medicine, economics, and linguistics, such models help make the educational process interactive and effective. The article also discusses the process of implementing simulation models, their advantages, and future development prospects.
Keywords: Simulation models, educational technologies, interactive learning, artificial intelligence, virtual reality, educational innovations, practical education, theoretical knowledge, simulation.